Role of Traditional Chinese Medicine in the Management of Viral Pneumonia - Xi, Shengyan; Li, Yunhong; Yue, Lifeng; Gong, Yuewen; Qian, Linchao; Liang, Tengxiao; Ye, Yong’an (Frontiers in Pharmacology, 2020)
Viral pneumonia is one kind of acute respiratory tract infection caused by virus. There have been many out-breaks of viral pneumonia with high contagiousness and mortality both in China and abroad, such as the great influenza in 1918, the severe acute respiratory syndrome (SARS) coronavirus in 2003, the Influenza A (H1N1) virus in 2009, and the Middle East Respiratory Syndrome coronavirus (MERS-CoV) in 2012 and the coronavirus induced disease (COVID-19) in 2019. These outbreaks and/or pandemic have significant impact on human life, social and economic development. Moreover, no specific drug has been developed for these viruses. Traditional Chinese medicine (TCM) plays an important role in the treatment of viral pneumonia during these outbreaks especially in SARS and COVID-19 because TCM herbal formulation can target several aspects of the diseases and have lesser side effects. In addition, in recent years, a lot of clinicians and researchers have made a series of in-depth exploration and investigation on the treatment of viral pneumonia with traditional Chinese medicine, which have understood TCM therapeutic mechanism more specifically and clearly. In order to provide reference for the treatment of viral pneumonia, this article reviews current understanding of the effects and mechanism of TCM for the treatment of viral pneumonia.